Meerkats united The impossible bird - Zunz, Marion; Brock, Richard; Miles, Hugh; Goss, Richard (Bristol : BBC [production company] ; Kuala Lumpur : Vision Four Home [distributor])
Documentary on meerkats in the Kalahari Desert. This film follows the lives of one band of these outrageous characters. Includes film of the ostrich filmed in Kenya, probes the remarkable world of this most unlikely bird.
Two spectacular films on one video
Editor, Tom Poore, Jim Cryan ; series producer, Dilys Breese, Peter Bale
Narrator: David Attenborough
Keywords: Meerkat -- Africa; Ostriches